EXPERIMENTAL DETERMINATION OF F-OH INTERDIFFUSION IN TREMOLITE AND SIGNIFICANCE TO FLUORINE-ZONED AMPHIBOLES - Brabander D.J.; Hervig R.L.; Jenkins D.M. (My University, 1995)
A hydrothermal-analytical procedure has been developed that allows for the quantitative study of anion exchange rates in hydrous silicates. This new procedure has provided the first opportunity to quantitatively investigate the kinetics of halogen-OH exchange reactions at subsolidus conditions. Handpicked, chemically homogeneous tremolite crystals were exposed to either F-rich or F-poor fluids at temperatures ranging from 500-800°C at 200 MPa (2000 bars), and the resulting concentration profiles were measured with either an electron microprobe or an ion microprobe. Critical to this procedure is the use of an aqueous silica-buffering assemblage (either quartz or forsterite + diopside + tremolite) in order to maintain the chemical and physical stability of the exposed crystal surfaces. Scanning electron microscope (SEM) photomicrographs taken before and after hydrothermal treatment show no evidence of dissolution reactions, consistent with a diffusion-controlled exchange process. For temperatures between 500 and 800°C, the Arrhenius relations for diffusion parallel to the c-crystallographic direction have an activation energy (Q) = 41 (+/-5) kJ/mole and (D0) = 3.4(+4.1-1.9) x 10-17 m2/s. Transport rates parallel and perpendicular to the c-axis are the same within the estimated uncertainties. Calculations indicate that F metasomatism by volume diffusion in amphiboles is relatively slow and may only play an important role in the evolution of a given hydrothermal system in the absence of faster processes such as chemical reaction. Knowledge of the Arrhenius relationships for F-OH interdiffusion allows one to extract information about the maximum duration of metasomatic or thermal events from F-zoned amphiboles. This procedure can be adapted to the study of other halogen-OH exchange reactions provided that the mineral stability is controlled by the dissolution of silica.